SEKOLAH â€œEMAK-EMAKâ€ UNTUK BUTA HURUF DI KECAMATAN LECES KABUPATEN PROBOLINGGO - Herman, Muthia Chaerani; Wardani, Novita Kusuma; Muhabbatillah, Sajidah; Purwasih, Joan Hesti Gita (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2018)
Illiteracy is the inability of individuals or citizens in terms of reading and writing words of words or sentences. Illiteracy does not only occur in Indonesia but has become a world problem for eradication. Illiteracy is closely related to the level of human resources quality owned by a country. Globalization is accompanied by advances in technology and information that demand the creation of quality and competent human resources. Consequently, developing countries are competing to eradicate illiteracy in their countries including Indonesia. In 2017 Indonesia still had 2.07%, equivalent to 3,387,035 residents experiencing illiteracy spread throughout the province. East Java Province is included in the category of people with illiteracy as many as 54,219 residents who incidentally are women. Therefore, the local government formed an institution for Community Learning Centers which could help efforts to eradicate illiteracy. This institution works with all elements of society so that the program designed can run well. This institution established a non-formal school located at the sub-district and village level to accommodate the illiteracy eradication learning program. The purpose of this study is to describe the efforts made by the PKBM institution in eradicating illiteracy, explaining the reasons for the participation of women in illiteracy eradication programs and the impact felt by women through literacy programs in the Leces sub-district. This study used case study with qualitative approach. The results of this study are the establishment of non-formal schools which are named